Peru : 2006 Article IV Consultation and Request for Stand-By Arrangement-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV Consultation with Peru and request for a Stand-By Arrangement highlights that the Peruvian economy has been reaping benefits of sound policies in a favorable external environment. The new government remains committed to sustaining fiscal consolidation to entrench macroeconomic stability while boosting infrastructure and social spending to decisively reduce poverty. Executive Directors commended the progress made in identifying foreign exchange-related credit risks in the banking system, and encouraged the authorities to implement their reform agenda aimed at reducing risks from dollarization.